Difficulties experienced by men during their partners’ pregnancy - Rosineide Santana de Brito; Joana D’arc Dantas Soares; Jovanka Bittencourt Leite de Carvalho; Danyelle Leonette Araújo dos Santos (Rev Rene, 2013)
Pregnancy causes physical and psychological changes in women, which directly affect the spouse. Thus, this study aimed at investigating the difficulties experienced by men during pregnancy, describing male reactions when facing such difficulties. This is an exploratory and descriptive study with a qualitative approach, developed in Natal / RN, Brazil. Data collection occurred from May to July 2008, with 27 men, through semi-structured interviews, after authorization n ° 176/2008 issued by the Ethics Committee of the Rio Grande do Norte Federal University. The interviews were elaborated according to Bardin’s Content Analysis. Results suggest that mood changes in pregnant women, alterations in marital life, financial hardship and access to health services are the main difficulties perceived by interviewed men. When facing such problems, respondents stated that they reacted calmly and understandingly. We concluded that the interviewees experienced difficulties resulting from their partners' pregnancy, but these did not represent an obstacle to their relationships within the family context.